2021
DOI: 10.3928/1081597x-20210812-01
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Quality of Life and Satisfaction After Refractive Lens Extraction Using a Diffractive Trifocal IOL: A Multicenter Retrospective Cohort Study

Abstract: PURPOSE: To assess patient satisfaction and quality of life after refractive lens exchange with a trifocal intraocular lens (IOL). METHODS: Consecutive patients who underwent refractive lens exchange with the AT LISA tri or AT LISA tri toric IOL (Carl Zeiss Meditec AG) at one of five surgical centers were surveyed for their quality of life and satisfaction after surgery using a standardized questionnaire. Patient responses were compared to patient chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Similarly, the research of Rementeria-Capelo et al also showed that the performance of trifocal toric IOLs is almost the same as that of nontoric versions on the same platform 69 . In addition, a study by Paul et al found that trifocal toric IOLs were also deemed highly satisfactory by people who received refractive lens exchange, but this study also found a high proportion of patients experiencing postoperative halo 70 .…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, the research of Rementeria-Capelo et al also showed that the performance of trifocal toric IOLs is almost the same as that of nontoric versions on the same platform 69 . In addition, a study by Paul et al found that trifocal toric IOLs were also deemed highly satisfactory by people who received refractive lens exchange, but this study also found a high proportion of patients experiencing postoperative halo 70 .…”
Section: Discussionmentioning
confidence: 67%
“…This confirms the ability of the toric multifocal IOL of providing not only an effective distance visual restoration, but also a functional visual rehabilitation at intermediate and near distances, as in previous studies. 2,8,11,12,[23][24][25][26][27][28] Mean monocular UIVA (66 cm) and UNVA (40 cm) values of 0.14 ± 0.11 and 0.03 ± 0.06 logMAR were obtained in the sample evaluated in the current study. Bilbao-Calabuig et al 11 found in a sample of 4282 eyes implanted with the AT LISA trifocal toric IOL a mean binocular UNVA measured at 40 cm of 0.05 ± 0.08 logMAR as well as a mean UIVA measured at 80 cm of −0.05 ± 0.14 logMAR.…”
Section: Discussionmentioning
confidence: 99%
“…1 For this reason, toric multifocal IOL designs have experienced significant development in the last few years, with a great variety of studies reporting the efficacy and safety of this type of implant. [2][3][4][5][6][7][8][9][10][11][12] Despite the excellent optical performance of current multifocal toric IOLs, 13,14 some factors can lead to a limitation of the visual outcomes with this type of implant. 15 Specifically, the main sources of error in toric IOL power calculation have been found to be the preoperative corneal measurement (27%) and IOL tilt (11.3%) and misalignment (14.4%).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in previous studies with AT LISA Tri, 15% and 8.3% of patients showed a great deal or inability to drive at night at 6 months and 6 years of follow-up, respectively. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in previous studies with AT LISA Tri, 15% and 8.3% of patients showed a great deal or inability to drive at night at 6 months and 6 years of follow-up, respectively. 23,24 No patients needed spectacles at far distance, and visual performance at intermediate distance was enough to achieve 97.6% spectacle independence. Spectacle independence at intermediate vision was not lower than that reported for extended depth-of-focus (EDOF) IOLs such as Symfony (Johnson & Johnson Vision) (between 84% and 89.1%) and Vivity (Alcon Laboratories, Inc.) (88%).…”
Section: Discussionmentioning
confidence: 99%